Fuzzy inference driven internet based bridge management system - Yadav, Deepesh; Barai, Sudhirkumar V. (Transport, 2005)
Bridges form an integral part of any country's transportation scheme, be it a railway network or a highway network. Periodic evaluation and subsequent maintenance can sometimes increase the life of a bridge to a great extent. Quantitative evaluation, however accurate, is too cumbersome, hence, in the present system the procedure of inspection is standardized and the analysis is done qualitatively. The qualitative data are converted to a mathematical format for the assessment by the use of popular Fuzzy logic approach. The whole system is based on the principle of evaluation from parts to the whole bridge structure. The method of calculation is based on Vertex method for fuzzy functions. The prototype system is the Internet based systemand it can be accessed from anywhere as long as the area has the Internet access. The prototype system is an attempt in the direction of an organized and well‐documented bridge management system.First Published Online: 27 Oct 2010